Is the U.S. Labor Market Really that Exceptional? A Review of Richard Freeman's America Works: The Exceptional U.S. Labor Market - Nickell, Stephen (Journal of Economic Literature, 2008)
America Works is a splendid book and Richard Freeman is to be congratulated on producing a work that sets out what is right and what is wrong with the U.S. labor market while being a joy to read. While I am generally sympathetic to both the analysis and the conclusions, there are a number of points of disagreement that I highlight in this review. In particular, I would add to his policy recommendations by taking a gamble and enacting a law that entitled all employees in the United States to four weeks paid holiday per year in addition to public holidays. This may transform summertime in the United States.